Researchers and resources rising to meet environmental challenges (Journal of EAHIL, 2025)
The article explores trends in environmental studies at the university-level and how EBSCO Information Services curates its database resources to meet the needs of students and researchers. The author discusses leading environmental problems and their cross-disciplinary permeance, the influence of international political agreements, and the varying needs of undergraduate students, graduate students, faculty, and library administrators. The history, content, and value of the GreenFILE and Environment Complete databases are detailed, including the many different subjects they cover (ex. climate change, green building, pollution, environmental protection, forestry, and watersheds.) The author articulates her process for reviewing and selecting scholarly journals to be included in these databases, and shares reasons for why the study of the environment is so important.